Modification of glass fiber catalyst surface by additional layers of silica and carbon nanofibers - Popov M.; Zazhigalov S.; Mikenin P.; Pisarev D.; Baranov D.; Lopatin S.; Zagoruiko A. N. Andrey Nikolaevich (2016, 2016)
Title screen